Biomass combustion in domestic boilers with low emissions - Gu, Quan (2020)
Compared with conventional fossil fuels, biomass has its unique advantages in terms of wide availability, potential high energy generation and carbon neutrality. Up to now, biomass combustion has made huge contributions to meet the heating demands of both commercial and domestic fields. However, one of the main challenges of biomass combustion is its pollution emissions, including NOx, CO and hydrocarbons. Meanwhile, the release of CO2 from biomass combustion which contributes to the greenhouse effect, should be paid more attention as well. The present PhD study aims to explore the combustion behaviours of biomass fuels by burning individual biomass pellets under different combustion atmospheres (air and oxy-fuel) and develop catalytic methods of NOx emission abatement for the potential use in small-scale and domestic biomass boilers.